Infectious interface keratitis (IIK) following lamellar keratoplasty: A literature review - Gao, Yan; Li, Chunhui; Bu, Ping; Zhang, Lijuan; Bouchard, Charles S. (The ocular surface, 2019)
The purpose of this study was to review the published incidence, etiology, clinical features and management of patients who developed infectious interface keratitis (IIK) following lamellar keratoplasty. This study is a systematic literature review. We conducted a systematic review of published Chinese and English report through a PubMed search with the medical subject headings using the following terms: corneal transplantation, keratoplasty, anterior lamellar keratoplasty (ALK), deep anterior lamellar keratoplasty (DALK), deep lamellar endothelial keratoplasty (DLEK), Descemet membrane endothelial keratoplasty (DMEK), Descemet stripping endothelial keratoplasty (DSEK), Descemet stripping automated endothelial keratoplasty (DSAEK), infectious interface keratitis (IIK), fungal keratitis, and bacterial keratitis. Data collected included patient demographics, surgical technique, clinical signs, treatment, outcomes, and donor rim cultures. A review of the relevant literatures was also undertaken. From 2007 to Feb. 2018, we identified 62 cases of IIK following lamellar corneal surgery. The mean age was 26.95 ± 8.80 years with a male/female ratio of 11:8 in DALK/ALK group and 69.65 ± 8.00 years with a male/female ratio of 17:16 in DSAEK/DSEK/DMEK group (no gender information for 10 cases). Of the 62 cases, 46 cases (75.41%) were fungal, 9 cases (14.75%) were bacterial, 2 cases (3.28%) were Actinomyces species, 1 case (1.64%) was acanthamoeba, and 4 cases (6.56%) were indeterminant. The mean onset of symptoms was postoperative day (POD) 49.47 ± 48.56 in DALK/ALK group, and 53 ± 112.01 in EK group, and 62.44 ± 50.07 for the bacterial keratitis, and 51.5 ± 102.42 for fungal keratitis. The mean postoperative follow-up period was 10.10 ± 9.36 months in DALK/ALK group and 12.37 ± 12.28 months in DSAEK/DSEK/DMEK group. Of the total 62 cases, 1 case (1.61%) with a Klebsiella pneumoniae positive donor rim cultures was associated with the same pathogen in the IIK, and 16 cases (25.81%) of fungal positive donor rim cultures were associated with the same pathogen in the IIK. Clinical signs included conjunctival injection, interface opacity, stromal edema for bacterial keratitis, and dense white infiltrates at the interface with endothelial plaques in some cases of fungal keratitis. Medical treatment included topical and oral antimicrobial agents. Surgical interventions included therapeutic keratoplasty. In 15 cases (24.19%), medical management was successful. Of the remaining 47 cases, 8 (12.90%) were managed with a repeat lamellar keratoplasty (LK) and 39 (62.90%) were unresponsive to conservative medical treatment and underwent a therapeutic keratoplasty (TKP). Post infectious best corrected visual acuity (BCVA) was logMAR 0 in 7 eyes (11.29%), better than or equal to logMAR 0.4 in 20 eyes (32.26%), less than logMAR 0.4 in 22 eyes (35.48%) and logMAR 0.7 or worse in 13 eyes (20.97%). In the rim culture negative group(n = 19), the average BCVA was logMAR 0.59 ± 0.68, with was logMAR 0.44 ± 0.74 in rim culture positive group (n = 15). There were three recurrence cases were reported after DMEK during the postoperative follow-up period. Infectious interface keratitis (IIK) is an uncommon complication of lamellar keratoplasty, but it can result in a substantial loss of vision or permanent blindness. Although graft infection can occur at any time following surgery, it most commonly (87%) occurred during the first 3 months postoperatively (54/62 cases). The most commonly reported causative organism of IIK following lamellar keratoplasty was C. albicans. Positive rim culture results can provide more rapid and appropriate treatment directed to the identified organism. Therapeutic keratoplasty (TKP) was the most common surgical procedure for the management of IIK. Visual outcomes post TKP are fair with 32.26% (20/62) of patients obtaining LogMAR 0.4 or better.